Sastra anak: media penumbuhan karakter kepemimpinan melalui ajaran Tamansiswa Ngerti, Ngrasa, Nglakoni (Tri Nga) - Siti Anafiah; Anang Sudigdo; Akbar Al Masjid (Universitas Sarjanawiyata Tamansiswa, 2022)
Character education for elementary school-age children can be applied through children's literary media. Unfortunately, it is still rare to find studies on this matter. This study aims to describe the character of leadership through Tamansiswa teachings based on Ngerti, Ngrasa, Nglakoni (Tri Nga) in children's literature. This type of research is descriptive. This study took the subject of children's literature of the type of folklore originating from Yogyakarta. The object of this research is the value of leadership character through the teachings of Tri Nga in children's literature. Researchers themselves are research tools. The tools in this research are data cards. Data collection uses reading and note-taking techniques. The data analysis method uses the padan and agih. The validity of the data in this study is interrater and interrater. The results of the research on the legend of Yogyakarta, there are several character values ​​appear, namely leadership and justice, independence and responsibility, and respect and courtesy. If these three characteristics are understood in children, they will grow respect, control emotions, and be able to interact with friends and the environment around them. This research is expected to contribute to preparing future leaders with a character starting with children using digital-based literature through the teachings of Tamansiswa Ngerti, Ngrasa, Nglakoni (Tri Nga). Keywords: Children's Literature; leadership character; Tri Nga